Interaction of RARRES1 with ICAM1 modulates macrophages to suppress the progression of kidney renal clear cell carcinoma - Geng, Xiaodong; Chi, Kun; Liu, Chao; Fu, Zhangning; Wang, Xu; Meng, Liangliang; Wang, Hanfeng; Cai, Guangyan; Chen, Xiangmei; Hong, Quan (Frontiers in Immunology, 2022)
Background: RARRES1 is a tumor suppressor protein, and its expression is suppressed in various tumor cells. However, whether it participates in the immune response in kidney renal clear cell carcinoma (KIRC) is unknown, and the defined mechanism is not clear. Therefore, the mechanism of RARRES1 in KIRC is worthy of investigation. Methods: We analysed the expression and function of RARRES1 with The Cancer Genome Atlas (TCGA) database. The Kaplan–Meier curve was adopted to estimate survival. RARRES1-correlated genes were obtained from the UALCAN database and subjected to Gene Ontology (GO) enrichment and protein–protein interaction (PPI) network analyses. The correlation analysis between tumor-infiltrating immune cells and selected genes were performed with TIMER database. We also investigated the possible function of RARRES1 in KIRC by coculturing Caki-1 cells with THP-1 cells. Immunofluorescence assay was performed to study the RARRES1 expression in difference grade KIRC tissues. Results: The expression of RARRES1 was negatively correlated with survival in KIRC patients. The GO biological process term most significantly enriched with the RARRES1-correlated genes was regulation of cell adhesion. ICAM1, which exhibited a relatively highest correlation with RARRES1, is positively correlated with the infiltration level of macrophages. RARRES1 could enhance the expression of ICAM1 in Caki-1 cells and then induce the activation of M1 THP-1 cells to decrease the viability and induce the apoptosis of Caki-1 cells. Conclusion: RARRES1 plays an antitumor role by promoting ICAM1 expression and inducing the activation of M1 macrophages. We offer insights into the molecular mechanism of KIRC and reveal a potential therapeutic target.